2007
DOI: 10.1681/asn.2006030269
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Is Associated with a Defect in Apical Receptor–Mediated Endocytosis in Mouse and Human Kidney

Abstract: Inactivation of the chloride channel cystic fibrosis transmembrane conductance regulator (CFTR) causes cystic fibrosis (CF).Although CFTR is expressed in the kidney, no overwhelming renal phenotype has been documented in patients with CF. This study investigated the expression, subcellular distribution, and processing of CFTR in the kidney; used various mouse models to assess the role of CFTR in proximal tubule (PT) endocytosis; and tested the relevance of these findings in patients with CF. The level of CFTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
97
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 44 publications
2
97
1
Order By: Relevance
“…A previous work from Jouret et al. (2007) also highlighted the association of higher urinary transferrin excretion with CFTR downregulation. These authors found a greater amount of transferrin in the urine of patients with cystic fibrosis, a genetic disease that is characterized by CFTR dysfunction (Jouret et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous work from Jouret et al. (2007) also highlighted the association of higher urinary transferrin excretion with CFTR downregulation. These authors found a greater amount of transferrin in the urine of patients with cystic fibrosis, a genetic disease that is characterized by CFTR dysfunction (Jouret et al.…”
Section: Discussionmentioning
confidence: 97%
“…2001; Jentsch 2005; Jouret et al. 2007; Souza‐Menezes et al. 2007; Jouret and Devuyst 2009; Carraro‐Lacroix et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probably involved in proximal tubule receptormediated endocytosis. Inactivation of CFTR leads to detection of significant, although variable, low molecular weight proteinuria in patients with CF (4). Nonetheless, there is no overt clinically relevant renal phenotype in children or teenagers with CF; however, asymptomatic nephrocalcinosis and hypercalciuria are present in up to 90 and 30% of individuals with CF, respectively (5).…”
mentioning
confidence: 99%
“…RT-PCR detection was performed with platinum TaqDNA polymerase (Invitrogen) for 32 cycles, and PCR products were visualized on a 1.5% agarose gel. Real-time quantitative PCR analyses were performed in duplicate by using iQ SYBR Green Supermix (Bio-Rad, Hercules, CA) (40). PCR conditions were 94°C for 3 min followed by 40 cycles of 30 s at 95°C, 30 s at 61°C, and 1 min at 72°C.…”
mentioning
confidence: 99%